Dominica : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2004)
The staff report for the Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility on Dominica focuses on macroeconomic framework and fiscal policy. The program has been based on the expectation that Dominica will achieve a collaborative debt restructuring with its creditors that meets the residual near-term financing needs and ensures medium-term debt sustainability. The authorities continue to make progress in implementing the structural reform agenda, which aims to address the root causes of the macroeconomic imbalances and to remove impediments to growth.